Limites do poder de fiscalização: construção do conceito de abuso do poder de fiscalização e identificação da melhor estratégia processual para combatê-lo - Maldonado, Luciano Burti (2016)
This study aims to define the limits of tax inspection power and thus, build the concept of abuse of the tax inspection power under Articles 195 and 196 of the National Tax Code, as well as defining the best legal strategy to fight it. Having this objective in mind, we will analyze the tax legislation regarding the supervisory procedures, especially at the federal level and the São Paulo State Finance. In order to understand the power of tax inspection, we will also make use of specialized doctrine on the subject. Once defined the inspection procedure rules and the power of the tax authorities, we will build the concept of abuse of tax inspection powers. Accordingly, in addition to the proposal for a normative concept we will also try to identify a pragmatic concept. Therefore, we investigate the perspective of taxpayers and the placement of administrative and judicial jurisprudence. The analysis of administrative and judicial jurisprudence in addition to assisting us in building the concept of abuse of the Inspection power under the pragmatic approach will also allow us to identify the strategies used by taxpayers to fight abuse of the oversight inspection power and, hence, define the best strategy to fight it, that is, whether during or after the tax inspection procedure and or through administrative defense or prosecution lawsuit.